Uncommon traveler : Mary Kingsley in Africa - Brown, Don, 1949- (Houghton Mifflin, 2000)
A brief biography of the self-educated nineteenth-century Englishwoman who, after a secluded childhood and youth, traveled alone through unexplored West Africa in 1893 and 1894 and learned much about the area and its inhabitants.